A pesquisa como princípio educativo no ensino de ciências : concepções e práticas em contextos brasileiros - Pauletti, Fabiana (2018)
This research presents the main concepts and survey practices as an educational principle in Science Teaching in Basic Education in Brazilian contexts. The question that guided this study was: What are the conceptions and survey practices as an educational principle in Science Teaching, in Basic Education in Brazil? Therefore, the general purpose it is to understand the research as an educational principle in the Science Teaching in Basic Education in Brazilian contexts. This is a theoretical study with a qualitative approach, whose survey´s method consists in a Literature Systematic Review (LSR). The work consisted in the identification of Brazilian PhDs researchers, with at least two productions, in the period from 2000 to 2015. The key-words, in addition, should mention the expression " Sciences teaching ", referring also expressions such as: "educating by the research", "survey in the classroom", "investigation in the classroom", "teaching by survey", "research in school", "education through research," "classroom with research," "investigative classes", " investigative class ", "teaching by investigation" and "learning by survey". Therefore, it was found 88 researchers from several regions of the country, with the exception of the North Region. The production of these researchers related to the theme, in this period, formed the analysis´ corpus, consisting qualified articles (Qualis/CAPES), books and book chapters and complete works in relevant events. The LSR of this corpus, plentifully detailed in the work, conducted, mainly, the two main conceptions of research as an educational principle in the context of the teaching of the Sciences, focused on the Basic Education, but may also extend to the Higher Education and in other areas: educating for research/survey in the classroom and teaching by investigation. These conceptions were characterized in order to clarify its vicinity and estrangements.